Prescription patterns of benzodiazepines in the Lebanese adult population - Ramadan, Wijdan H. (2016)
This study assessed the profile of benzodiazepine (BDZ) users in Lebanon. Adult patients visiting the pharmacies with prescriptions of BDZs were included in the study. Seven hundred and eighty-six current BDZ users were included, of whom 54.2% were females. Twenty-three percent reported being alcohol consumers and were mostly males. The two most commonly used BDZs were alprazolam (34.6%) and bromazepam (33.6%). The indication for use was mainly anxiety (44.4%), insomnia (22.5%), and depression (15.9%). The prescribing physicians were primarily psychiatrists (43.2%), followed by general practitioners (29.7%). Forty percent had been taking the drug for more than a year. Among those using BDZs for at least 1 month, 35.5% increased the dose with time. Thirty-three percent reported having experienced side effects. Eighteen patients (2.3%) reported taking more than one BDZ concomitantly, while 18.3% were taking drugs that should not be prescribed along with BDZs. In conclusion, the use of BDZs is highest among females, especially for the treatment of anxiety. Moreover, continuous use of the drugs for more than a year as well as significant potential drug interactions was identified.